El control de convencionalidad en el ámbito del Poder Ejecutivo y el acto administrativo inconvencional. Pautas interpretativas de la CIDH (2012-2020) ; The control of conventionality in the area of the Executive Branch and the unconventional administrative act. Interpretive guidelines of the IACHR (2012-2020) - Monge, Natalia Leonor (2024)
Este trabajo se centra en la identificación, descripción y análisis de las construcciones argumentales elaboradas por la Corte Interamericana de Derechos Humanos en torno al control de convencionalidad. Entre otros aspectos, se analizará el desarrollo que de esta práctica y sus notas distintivas realiza el Tribunal desde el año 2012 al 2020. El tema se enmarca en el control de convencionalidad aplicado por el Poder Ejecutivo en el ejercicio de la función administrativa; pero, centralmente, pretende visibilizar el acto administrativo inconvencional como efecto. Como problema, se advierte que el control de convencionalidad en contadas ocasiones constituye una práctica diaria en la interpretación del derecho doméstico en el ámbito del referido poder público. En efecto, una de las causas que envuelve a esta problemática obedece a que los casos son resueltos al amparo de la Constitución y de la ley, pero se pasa por alto que el principio de juridicidad en sede administrativa se ve ampliado a partir de la jerarquización de los tratados internacionales de derechos humanos. This work focuses on the identification, descrip tion and analysis of the argumentative constructions developed by the Inter-American Court of Human Rights around the control of conventionality. Among other aspects, the development of this practice and its distinctive notes made by the court from 2012 to 20201 will be analyzed. The topic is framed in the control of conventionality applied by the Executive Branch in the exercise of the administrative function but, centrally, it aims to make visible the unconventional administrative act as an effect. As a problem, it is noted that conventionality control rarely constitutes a daily practice in the interpretation of domestic law in the scope of the aforementioned public power. In fact, one of the causes of this problem is that cases are resolved under the protection of the Constitution and the law, but it is overlooked that the principle of legality in administrative headquarters is expanded from the hierarchization of international human rights treaties. Based on the above, the objective of this work is not to stop at analyzing the causes that motivate the little use of conventionality control at administrative headquarters but to start from the beginning, that is, to affirm that from the regulatory and jurispru dential point of view the Public Administration bodies are obliged to carry out a conventionality control in the exercise of the administrative function. In other words, it should be a daily practice for each sector to determine whether or not the norm that is being reviewed complies with what is determined by the American Convention on Human Rights or with the interpretation made by the Inter-American Court.